Analysis of Sinoman Principles as Marriage Readiness in Teenagers - Sesya Dias Mumpuni; Dita Efani; Winahyu Destyarti; Indra Tirto Aji (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
Marriage is a lifelong worship who believe it, people in the world always want married just once in their life, but this desire is very rarely accompanied by readiness. Good preparation for marriage can be indicated when conducting an assessment between couple male and female in premarital counseling by applying the Sinoman principle as a preventive service in counselling. The aims of study to find the readiness of a prospective married couple by applying the Sinoman principle. This research uses descriptive quantitative research method use a sample of 70 respondents Google Form questionnaire to prospective married couples combining the level of recognition, readiness to accept and the reciprocity of the couple with the variables in this study, namely relationship conditions, adolescent love, wedding preparations, pager ayu, ladhen wedhang and rewang. The results of the validity the r table obtained was 0.235 with a reliability coefficient of ? = 0.0937. The conclusion of this study is marriage preparation is something that must be considered as best as possible, through premarital counseling, the goal of helping to minimize problems in a marriage, not only during marriage but also in married life.